TANTANGAN GURU DI ERA MILENIAL - Nurmansyah (El-Hamra, 2018)
The millennial era has characteristics where students can quickly access information. This is so, making the figure of a teacher no longer the only person who is most well informed of various information and knowledge that is growing, developing. Responding to the conditions of students in the mileneal era, the world of education requires teachers who are able to guide, direct and who are clearly able to filter or filter out things that are not suitable for children's consumption.Key Words: Teacher challenges, millennial era